1996
DOI: 10.1017/s0376892900038844
|View full text |Cite
|
Sign up to set email alerts
|

Food for all in 2020: can the world be fed without damaging the environment?

Abstract: SummaryApproximately 780 million people world-wide arc chronically undernourished, and past gains in food production have been associated with environmental problems, yet global demand for cereals is projected to increase by 56% and for meat by 74% between 1990 and 2020.The International Food Policy Research Institute has developed the view that every person in the world can have access to sufficient food to sustain a healthy and productive life, that malnutrition can be abolished, and that food can originate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

1999
1999
2021
2021

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 1 publication
1
6
0
Order By: Relevance
“…The average utilization of inputs is 77.72 kg with standard deviation of 70.12 and its average cost is Birr 1056.00 with standard deviation of 1036. When we look up on the strength of the linear association between the fertilizer used and agricultural production through Pearson correlation, it is strong and positive with Source: survey result, 2015 p-value of 0.000 (significant at 0.01 level, 2-tailed) which is in line with the previous research result of intensive high-yield agriculture is dependent on addition of fertilizers [27] (Figure 2).…”
Section: Application Of Agricultural Inputs Vs Agricultural Productionsupporting
confidence: 86%
“…The average utilization of inputs is 77.72 kg with standard deviation of 70.12 and its average cost is Birr 1056.00 with standard deviation of 1036. When we look up on the strength of the linear association between the fertilizer used and agricultural production through Pearson correlation, it is strong and positive with Source: survey result, 2015 p-value of 0.000 (significant at 0.01 level, 2-tailed) which is in line with the previous research result of intensive high-yield agriculture is dependent on addition of fertilizers [27] (Figure 2).…”
Section: Application Of Agricultural Inputs Vs Agricultural Productionsupporting
confidence: 86%
“…The action programme outlined earlier will require all relevant partiesindividuals, households, farmers, local communities, the private sector, civil society, national governments and the international community -to work together in new or strengthened partnerships; it will require a change in behaviour, priorities and policies; and it will require strengthened cooperation between developing and industrialized countries and among developing countries. The world's natural resources are capable of supporting sustainable food security for all people, if current rates of degradation are reduced and replaced by appropriate technological change and sustainable use of natural resources (Pinstrup-Andersen and Pandya-Lorch, 1996a).…”
Section: Discussionmentioning
confidence: 99%
“…Food self-sufficiency can be achieved if food needs can be met by domestic production (Ewing-Chow & Vilarasau Slade, 2012;Pinstrup-Andersen & Pandya-Lorch, 1996;Syemin, 2010). When referring to this definition, it can be concluded that in the period 2018-2022 Indonesia can achieve corn selfsufficiency.…”
Section: *Predictionmentioning
confidence: 99%